Enhancing Descriptive Writing Skills in Junior High School Students through Effective Outlining Strategies - Azzah S, Iftinan R; Damayanti, Mifa Dita; Afni, Sebtia Rizki Nur (Institut Agama Islam Negeri Palopo, 2025)
This study investigates the effectiveness of the outlining strategy in teaching descriptive text writing to seventh-grade students, within the context of English language learning at MTsN 8 Kediri. With the challenge of mastering productive skills such as writing in a second language, this research identifies the need for engaging and systematic instructional strategies to facilitate students' learning process. A quasi-experimental design involving 55 seventh graders was employed, comparing the outcomes of an experimental group taught using the outlining strategy against a control group utilizing mind mapping techniques. Data were collected through pre-test and post-test measures and analyzed using ANCOVA in SPSS 25. Results indicated a significant improvement in the experimental group's writing skills, with mean scores rising from 48.57 to 82.75, compared to the control group's increase from 48.22 to 81.37. Furthermore, ANCOVA results confirmed the outlining strategy's effectiveness with a value of p=0.009 (p < α 0.05). The study's findings align with Vygotsky's theory on the development of written language, highlighting the outlining strategy's role in enhancing cognitive development through internal organization of thoughts (inner speech), utilization of socio-cultural tools, and operation within the learners' Zone of Proximal Development (ZPD). These outcomes underscore the importance of structured, supportive instructional strategies in teaching practices, illuminating the outlining strategy's potential to improve written language acquisition among junior high school students significantly